"Diminishing returns" for leaves of five age‐groups of Phyllostachys edulis culms. Issue 9 (27th September 2021) - Guo, Xuchen; Shi, Peijian; Niinemets, Ülo; Hölscher, Dirk; Wang, Rong; Liu, Mengdi; Li, Yirong; Dong, Lina; Niklas, Karl J.
Abstract: Premise: Leaf mass ( M ) and lamina surface area ( A ) are important functional traits reported to obey a scaling relationship called "diminishing returns" (i.e., M ∝ A α >1 ). Previous studies have focused primarily on eudicots and ignored whether the age of leaves affects the numerical value of the scaling exponent (i.e., α ). Methods: The effect of age was examined using 1623 Phyllostachys edulis leaves from culms differing in age collected in Nanjing, China. The scaling relationships among leaf A, fresh mass (FM), and dry mass (DM) were evaluated using reduced major axis protocols. The bootstrap percentile method was used to test the significance of differences in α ‐values. Results: Overall, the numerical values of α exceeded 1.0. The scaling relationship between FM and A was statistically more robust than that between DM and A . The scaling exponents of FM vs. A exhibited a "high‐low‐high‐low‐high" numerical trend from the oldest to the youngest age‐group. FM increased linearly as culm age decreased; the leaf DM per unit area (LMA) exhibited a parabolic trend across the age‐groups. Conclusions: "Diminishing returns" is confirmed for all but one age‐group of an important monocot species. The relationship between FM and A was statistically more robust than that between DM and A for each age‐group. The FM per unit A decreased with increasing age‐groups, whereas the middle age‐groups had a greater LMA than the oldest and youngest age‐groups. These data are the first to show that the age of shoots affects the scaling relationship between leaf mass and area.